The rules of purposes and its relationship with the fundamentalist rules - Mohd Borhanuddin, Zakaria (2020)
The problem of research emerges in explaining the relationship between the rules of the purposes and the fundamentalist rules، the extent of their connected and their importance for jurist to devise provisions for cases which there is no legal text، and it aims to clarify the concept of legitimate purposes of old and late jurists، and its importance in Islamic legislation without excessive or inattentive، and the approach followed: describe The rules of purposes by explaining their definition and establish them to be a guide that the jurist argues in the cases which there is no legal text، with an indication to the manifestation of its characteristics and the most prominent benefits ، and analyze of the relationship between them and fundamentalist rules and the statement of aspects of agreement and separation، so the researcher reached to that the rules of purposes are a major of rules denoted by the sum of the partial evidence and taken to the rank of independent major evidence، and it was a valid argument and can be a valid inference by it، and it is with fundamentalist rules are two basic pillars which the jurist is relying on in order to reach the Islamic legal ruling that the legislator wanted and desired. And who was not full conversant in the rules of the purposes will not be able to employ the fundamentalist rules as required.